Correction: Enciu et al. Is Complete Excision Always Enough? A Quality of Sexual Life Assessment in Patients with Deep Endometriosis. Medicina 2024, 60, 1534 - Raluca Gabriela Enciu; Octavian Enciu; Dragoș Eugen Georgescu; Adrian Tulin; Adrian Miron (Medicina)
In the original publication [...]